As dimensões simbólicas do vestuário - Carvalho, Janice Leal de (2008)
In the clothing marketing field, the understanding of the consumer’s attitudes and buying behavior relating to the fashion apparel is an essential condition for introducing new products on the market. In that context we intended to study the symbolic dimension of the fashion apparel consumed by young female executives, widening the comprehension in this research field. This study refers to young female executives who work in the city of Fortaleza. The selection of the participants was initially made through lists of members of the two main associations that congregate young business men. Observing that the clothing choice works as a non-verbal way of communication, this production contributes in the persecution of understanding the symbolic dimension of fashion apparel consume by young female executives and show its significance to the contemporary woman as a way of expression and social interaction. The research methods used were exploratory and descriptive studies. Therefore, the descriptive research was chosen, considering a single transversal study with the adoption of quantitative techniques. A priori, the research results were depurated with simple frequency analyses, so as to delineate the sample. Subsequently, for identifying the factor structures relating to the attitude items, the factorial analyses was used, which identified the existence of five dimensions relating to the attitude concerning the buying of fashion apparel.